PELATIHAN PEMBUATAN SABUN CUCI PIRING DAN CUCI TANGAN DI POSYANDU DISABILITAS – DESA. BEDALI – KECAMATAN LAWANG - KABUPATEN MALANG - Hadi Priyo Sudarminto; Anang Takwanto; Rosita Dwi Chrisnandari; Sandra Santosa; Arief Rahmatulloh (Publisher UPT P2M Politeknik Negeri Malang, 2022)
The purpose of this PKM is to provide training on making dish soap and hand washing to the Posyandu with Disabilities in Bedali Village. It is hoped that this training will encourage the interest and creativity of the members of the Posyandu with disabilities to become entrepreneurs. The output of this PkM is an increase in partner skills, partner HR competitiveness, and appropriate technology. PKM activities began with the procurement of tools and materials for making soap, making soap-making video tutorials, implementing soap-making training activities at the Posyandu group of Posyandu with Disabilities in Bedali Village which was carried out by taking into account K3 aspects and the Covid-19 health protocol.